Katalog zaključnih del študentov FGPA s področja BIM (University of Maribor Press, 2017)
Catalog of Work of Graduate Students FGPA from BIM. Building Information Modeling (BIM), as a modern approach in a built environment, combines the fields of construction, architecture, mechanical engineering and other fields related to construction projects using information and communication technologies. BIM’s approach is an information model of a building, which with all the collected information represents an increase in quality, accuracy and accessibility to information throughout the life cycle of construction projects. With BIMpristop, processes (process model) and individual blocks of the building object (object model) in building projects in all stages of the process are improved. Such an approach comprehensively addresses construction projects from their conceptual design, geometric representation of the building, functional purpose, structural and energy analysis, placement into space, until their realization, and later when used and ultimately in decomposition. The responsibility of the Faculty of Civil Engineering, Traffic Engineering and Architecture of the University of Maribor (FGPA UM), whose primary activity is the education and training of future personnel, is constantly increasing in the ongoing research and development of new modern forms of knowledge acquisition. Therefore, the content of study programs is constantly adapting to new trends in the construction industry. The enthusiasm and interest of students is greatly contributed to this by the enthusiasm and interest of students who, together with their mentors and co-mentors in their final work, give new, often unexplored, fields of construction projects with a modern BIM approach. The present e-publication titled FGPA Final Results Catalog in the field of BIM provides summaries of the graduate, master’s and doctoral students who are or will be shortly finishing their studies at FGPA and whose final work deals with the BIM approach. The purpose of the e-publication is the promotion of students, and consequently also FGPA, and can be at the same time a source of information for companies with the vision of introducing BIMpristop, in finding the qualified cadres they need to achieve the set development goals.